The experiences and perceptions of police members regarding the effectiveness of trauma debriefing within the South African Police Service - Terblanche, Lourie (University of Pretoria, 2013)
Dissertation (MSoc.Sci (Employee Assistance Programme))--University of Pretoria, 2006.